Safety and Effectiveness of the Denali Inferior Vena Cava Filter: Intermediate Follow-Up Results. (August 2016) - Reis, Stephen P.; Kovoor, Jerry; Sutphin, Patrick D.; Toomay, Seth; Trimmer, Clayton; Pillai, Anil; Reddick, Mark; Kalva, Sanjeeva P.
Purpose: The purpose of the study is to evaluate the clinical safety and effectiveness of the Denali (Bard, Tempe, Arizona) retrievable inferior vena cava (IVC) filter. Materials and Methods: In this retrospective study, authors reviewed the data of Denali IVC filters placed at their institution between 2013 and 2015. The clinical presentation, indications, and procedure-related complications during placement and retrieval were evaluated. The frequency of post filter pulmonary embolism (PE) and filter-related complications was assessed. Results: Denali filters were placed in 87 patients (47 males; mean age: 56 years). Twenty patients presented with PE, 45 with deep vein thrombosis (DVT), and 21 with both PE and DVT, 1 filter was placed prophylactically before surgery. Indications for filter placement included contraindications to anticoagulation (AC; n = 80), failure of AC (n = 4), and complications of AC (n = 3). No patients had PE on follow-up imaging after filter placement. Retrieval was attempted in 31 patients after a mean period of 125 days (range: 34-324 days). The filter was successfully removed in 31 (100%) patients. Follow-up imaging, available in 71 (82%) patients (range: 2-538 days), demonstrated penetration of 15 legs in 5 patients, caval thrombus in 3, 1 resulting in caval occlusion, <15° filter tilt in 5, and no leg fractures or crossed legs. Conclusion: The Denali filter is safe during deployment and readily retrievable. The overall safety following deployment is similar to those reported in the literature, and the incidence of filter fractures and migration appears to be less than the previous generation of Bard devices.